2007
DOI: 10.2118/86504-pa
|View full text |Cite
|
Sign up to set email alerts
|

Diversion and Cleanup Studies of Viscoelastic Surfactant-Based Self-Diverting Acid

Abstract: Summary A self-diverting-acid based on viscoelastic surfactant (SDVA) has been successfully used recently on numerous stimulation treatments of carbonate formations in various fields. The decrease of acid concentration during the spending process viscosifies the fluid through the transformation from spherical micelles to an entangled wormlike micellar structure while penetrating the carbonate rock. The highly viscous fluid acts as a temporary barrier and diverts the fluid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…The optimum flow rate was 10 cm 3 /min. The existence of optimal flow rate was consistent with the results of Hoefner et al (1987) and Wang et al (1993) for regular acids, and those of Lungwitz et al (2007) for surfactant-based acids. The latter authors noted a minimum at 1 cm 3 /min.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The optimum flow rate was 10 cm 3 /min. The existence of optimal flow rate was consistent with the results of Hoefner et al (1987) and Wang et al (1993) for regular acids, and those of Lungwitz et al (2007) for surfactant-based acids. The latter authors noted a minimum at 1 cm 3 /min.…”
Section: Resultssupporting
confidence: 86%
“…Lungwitz et al (2007) demonstrated that cleanup of retained surfactant in carbonate cores by 2 wt% KCl brine or 10 vol% mutual solvent could result in high permeability regain. A few treatments, however, produced results below expectations (Nasr-El-Din et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in the chemical literature have established that inorganic particles can be added to wormlike micelles to enhance the solution viscosity. For example, barium titanate pyroelectric nanoparticles increase the viscosity of solutions composed of sodium fatty acid methyl ester sulfonate (Luo et al 2012). Bandyopadhyay and Sood (2005) studied the rheology of semidilute solutions of the cationic surfactant cetyl trimethylammonium tosylate (CTAT) in the presence of silica colloids with diameters of 0.1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…This occurred as a direct result of the effective diversion of acid that was achieved by the VES formulation. Lungwitz et al (2007) experimentally studied the use of VES based fluids as diverting systems in acidizing treatments. They performed coreflood experiments using carbonate core samples with permeability in the range of 0.1 to 50 md at a temperature of 200 to 240°F using 15 wt% HCl acid systems.…”
Section: B1 Experimental Studiesmentioning
confidence: 99%